Regulation of glycogenesis and glycogenolysis in contracting skeletal muscle - Lutoslawska, G.; Malara, M. (Human Movement, 2004)
Intramuscular glycogen provides energy during intensive and prolonged muscular work. It is well established that in a cell glycogen represents a precisely organized structure named glycosome and containing glycogenin . an autocatalytic protein, glycogen proper, and the key enzyme of glycogen synthesis . glycogen synthase. Glycosomes are localized in different cell compartments (intramyofibrillary, connected with the sarcoplasmic reticulum) and differ with respect to their size (pro- and macroglycogen). Both the structure and location of glycosomes play a substantial role in the regulation of intramuscular glycogen metabolism, providing energy for contraction but also for sodium/potassium transport. Glycogen synthesis and breakdown are precisely regulated by a system of protein kinases and phosphatases, phosphorylating and dephosphorylating key enzymes . glycogen synthase and glycogen phosphorylase. Phosphorylation of enzymes results in a decrease of glycogen synthase and in an increase in the glycogen phosphorylase activity; the inverse effect of dephosphorylation occurs for both enzymes. Glycogen phosphorylase is activated by the calcium protein kinase on the onset of contraction. Additionally, it seems feasible that 5.-AMP accumulation in contracting muscle and activation of the 5.-AMP-activated protein kinase (AMPK) inhibit the glycogen synthase activity. In consequence, it is postulated that mainly glycogenolysis but not glycolysis is a critical step in carbohydrate metabolism in working muscle. On the other hand, a number of studies indicate that the glycogen synthase activity is elevated in contracting muscle. Although the significance of this phenomenon for energy metabolism is unknown, it is postulated that the increase in glycogen synthase during contraction is responsible for the first rapid and insulinindependent phase of glycogen resynthesis after contraction.